‘And Now the Biography’: 150 Years of ‘Telegraph’ Todd - Cryle, Denis (Journal of Telecommunications and the Digital Economy, 2018)
Sir Charles Todd is a seminal nineteenth-century figure who continues to fascinate popular writers and scholars alike, not least those working in modern telecommunications. A well-attended symposium, convened by Adelaide societies in August 2012, paid lengthy tribute to his wide-ranging achievements. In his own lifetime, ‘Telegraph’ Todd was celebrated for his achievement in planning and organising the construction of the Overland Telegraph Line from Adelaide to Darwin, linking Australia to the outside world. His personal intervention on the hazardous Northern Territory leg of the Overland Telegraph’s construction was hailed as decisive in the successful completion of one of the great engineering feats of its day. Yet Todd himself has remained a shadowy figure, eluding a series of biographers for more than a century after his death. This article concerning the genesis of Todd’s recent biography entitled Behind the Legend: The Many Worlds of Charles Todd, examines changing historical perspectives on Todd and his achievements. In particular, it identifies the increasing availability of biographical resources over time and reviews the challenges which biographers faced in bringing to life the career of a great pioneering Australian.